2013
DOI: 10.1371/journal.pone.0069009
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Endothelial Expansion Promoted by Human Bone Marrow Mesenchymal Stem Cell-Derived Conditioned Medium

Abstract: Healthy corneal endothelium is essential for maintaining corneal clarity, as the damage of corneal endothelial cells and loss of cell count causes severe visual impairment. Corneal transplantation is currently the only therapy for severe corneal disorders. The greatly limited proliferative ability of human corneal endothelial cells (HCECs), even in vitro, has challenged researchers to establish efficient techniques for the cultivating HCECs, a pivotal issue for clinical applications. The aim of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 34 publications
0
75
0
2
Order By: Relevance
“…Mesenchymal stem cell-conditioned medium was prepared as previously described. 28 The HCECs were cultured by using MSC-conditioned medium at 378C in a humidified atmosphere containing 5% CO 2 , and the culture medium was changed twice per week. The HCECs were passaged at ratios of 1:3 by using 10x TrypLE Select (Life Technologies) at 378C for 12 minutes when they reached confluence.…”
Section: Cell Cultures Of Hcecsmentioning
confidence: 99%
“…Mesenchymal stem cell-conditioned medium was prepared as previously described. 28 The HCECs were cultured by using MSC-conditioned medium at 378C in a humidified atmosphere containing 5% CO 2 , and the culture medium was changed twice per week. The HCECs were passaged at ratios of 1:3 by using 10x TrypLE Select (Life Technologies) at 378C for 12 minutes when they reached confluence.…”
Section: Cell Cultures Of Hcecsmentioning
confidence: 99%
“…16 An additional complication is that the proliferative ability of HCECs is limited even under ideal culture conditions, so multiple procedures have been developed to promote cell proliferation. [29][30][31][32] For instance, we reported that the use of a ROCK inhibitor, 13 conditioned medium derived from mesenchymal stem cells, 14 and laminin 511 fragment as a culture substrate 17 enhances cell proliferation. In the current study, we screened several low-molecular-weight compounds and found that the p38 MAPK inhibitor, SB203580, promotes cell proliferation while maintaining cell density and functional properties.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal endothelial growth medium was prepared by conditioning basal medium mix (OptiMEM-I, 8% fetal bovine serum [ 14,16 Briefly, confluent 3T3 fibroblasts were incubated with 4 lg/mL mitomycin C (MMC) (Kyowa Hakkko Kirin Co., Ltd., Tokyo, Japan) for 2 hours, seeded on plastic dishes at a cell density of 2 3 10 4 cells/cm 2 , and cultured with DMEM (Life Technologies Corp., Grand Island, NY, USA) supplemented with 10% FBS, 100 U/mL penicillin, and 100 lg/mL streptomycin (Nacalai Tesque, Inc., Kyoto, Japan). The 3T3 fibroblasts were washed 3 times with PBS and cultured with basal medium mix for an additional 24 hours.…”
Section: Cell Culturesmentioning
confidence: 99%
“…It is estimated that the adult primary CECs can be passaged around four times, and there is little improvement even with modified medium and supplemented cytokines [43]. Yet, several protocols are developed to promote the proliferation of CECs, including the use of human bone marrow mesenchymal stem-cell-derived conditioned medium [44], or human amniotic epithelial-cell-derived conditional medium [45] (Table 2). In addition, telomerase or Cdk4R24C (constitutively active mutant form of Cdk4) and CyclinD1 transduction into CECs showed in vitro pump function [46,47].…”
Section: Cell Sources For Corneal Endothelial Diseasesmentioning
confidence: 99%
“…[40][41][42][43][44][45] Establishment of CEC cell lines CEC lines were generated by transduction of telomerase or Cdk4R24C (constitutively active mutant form of Cdk4) and CyclinD1 gene. [46,47] Fetal human CEC Fetal CEC culture Protocol of primary culture, passage and freezing fetal CECs.…”
Section: Adult Human Cecsmentioning
confidence: 99%